Australia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Australia has enjoyed a comparatively robust economic performance while adjusting to the end of the commodity price and mining investment booms of the 2000s. The recovery from these shocks has advanced further in 2017. Aggregate demand has been led by strong public investment growth amid a boost in infrastructure spending and private business investment has picked up, but private consumption growth has remained subdued. Employment growth has strengthened markedly over the year, although the economy is not yet back at full employment. Wage growth is weak and inflation is below its target range. The macroeconomic policy stance has become more supportive with the infrastructure investment boost.